Strategi Pemberdayaan Ekonomi Lokal Melalui Optimalisasi Potensi Gerabah Erri Art di Desa Negara Ratu - Nayla Nurlitha; Diana Chandra Olivia; Nikmatunnasikhah Nikmatunnasikhah; Viada Chrisellia; Aldi Saputra (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2026)
Empowering the local economy at the village level is a key effort in improving community welfare through the sustainable utilization of existing resources. Negara Ratu Village has a pottery craft sector with strong economic and cultural value, yet it still faces several obstacles, such as limited innovation, suboptimal marketing, and minimal use of digital media. This program aims to enhance the economic and social capacity of Gerabah Erri Art artisans through digital marketing assistance, branding reinforcement, and the implementation of pottery educational classes. The method applied was Participatory Action Research (PAR), which directly involved the artisans in every stage of the activity. The program was carried out through the development of an educational module on pottery, the creation of digital promotional materials, the preparation of a product catalog, and the activation of social media accounts as an initial publication platform. In addition, a trial pottery workshop was conducted with participants from outside the village. The results show improvements in digital promotion skills, expanded market reach, strengthened business identity, and emerging opportunities to develop craft-based educational tourism. Therefore, this program has a positive impact on strengthening the local economy and supporting the sustainability of the pottery industry in Negara Ratu Village.